Time pressure preferences - Thomas Buser; Roel Van Veldhuizen; Yang Zhong (Lund University, School of Economics and Management, Department of Economics, 2022)
Many professional and educational settings require individuals to be willing and able to perform under time pressure. We use a lab experiment to elicit preferences for working under time pressure in an incentivized way by eliciting the minimum additional payment participants require to complete a cognitive task under various levels of time pressure versus completing it without time pressure. We make three main contributions. First, we document that participants are averse to working under time pressure on average. Second, we show that there is substantial heterogeneity in the degree of time pressure aversion across individuals and that these individual preferences can be partially captured by simple survey questions. Third, we include these questions in a survey of bachelor students and show that time pressure preferences correlate with future career plans. Our results indicate that individual differences in time pressure aversion could be an influential factor in determining labor market outcomes.
Keywords: C90; D91; J22; 330; Time Pressure; Experiment; Gender